KONFLIK DAN INTEGRASI SOSIAL (Studi Tentang Perbedaan Pemahaman Ajaran Islam antara Muhammadiyah dan Nahdlatul Ulama di Desa Ngunut Kecamatan Babadan Kabupaten Ponorogo - Ahmad Muslih (MUADDIB Jurnal Kependidikan dan Keislaman, 2013)
The difference of understanding Islamic between Muhammadiyah and NU in Ngunut, Babadan, Ponorogo are conflict miniature and social integration. The research is using qualilatif approach and observation method, interview and documentation. The conflict was happened when there is someone felt low confident, sin, more over they feel that influence and dominance decrese. The social integration was happened when the new aqidah appear as communicator increase of level education and the appear of defiance. The negative effect of the conflict is appearing of polarization on society suspicious, negative perception, and selfirh. Whereas, the positif effect of the conflict is corroborate of enthusiarm group, dynamicazation society, corroborate identity and there is appear of coordinating uniter.